2022
DOI: 10.5539/ibr.v15n5p21
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Determining Factors of Financial Distress (A Case Study at PT. Bank Rakyat Indonesia (Persero)

Abstract: Economic misery is a circumstance in which the debtor can not satisfy his/her duties to creditors after they fall due. economic distress is the country of the company experiencing economic problems and is threatened with financial ruin. The motive of this study become to decide the impact of Capital Adequacy Ratio (vehicle), Operational costs on working profits (BOPO), Non appearing Loans (NPL), loan to Deposite Ratio (LDR), and go back On belongings (ROA) on monetary distress. This studies changed into conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Companies must be able to suppress their operational activities so that the funds used can create profits from other activities. The research results are supported by, (Suidarma et al, 2022) and (Asyikin et al, 2018). According to (Zahronyana & Mahardika, 2018).…”
Section: The Effect Of Oeoi On Financial Distressmentioning
confidence: 54%
See 1 more Smart Citation
“…Companies must be able to suppress their operational activities so that the funds used can create profits from other activities. The research results are supported by, (Suidarma et al, 2022) and (Asyikin et al, 2018). According to (Zahronyana & Mahardika, 2018).…”
Section: The Effect Of Oeoi On Financial Distressmentioning
confidence: 54%
“…The OEOI variable which has a positive (+) indicates that an increase in OEOI has resulted in sharia commercial banks tending to experience financial distress. According to (Suidarma et al, 2022) Based on the results of the study, the significance of the value of workload on operating profit (OEOI) is less than 0.05. So it can be concluded that the variable running fee on working profit (OEOI) has an effective effect on monetary distress.…”
Section: Operating Expenses Operating Income (Oeoi) Affect To Financi...mentioning
confidence: 99%